Institutional Leadership or Institutional Overreach? : Overriding the Parties’ Agreement for the Number of Arbitrators in Expedited Proceedings - Chong, Daniel LING Tien (American Journal of Trade and Policy, 2020)
The institutions of international arbitration have played an increasingly active role in arbitral governance. The claim that they merely provide administrative services no longer holds water. With the ability to amend institutional rules, update practice guidelines, and revise institutional practices, they wield the power to efficiently effect change – a power that no other actor in international arbitration comes close to having.However, it has been said that in their quest to lead change, some institutions have overstepped their mandate and overreached their powers. Based on a variety of primary and secondary sources, this article examines the situations in which institutions have overridden the parties’ agreement for the number of arbitrators appointed in cases of expedited proceedings. Thereafter, it seeks to analyze whether institutions, in a bid to push progress have overstepped their authority.
Keywords: International Arbitration; Arbitral Institutions; Overriding Party Autonomy; Expedited Proceedings; Number of Arbitrators; New York Convention